PENINGKATAN KUALITAS PENDIDIKAN MELALUI PEMBELAJARAN BERBASIS SISWA - Jamaluddin Jamaluddin (Jurnal Ilmiah Didaktika, 2011)
The quality of education can be enhanced through the development of learning processwhich in turn will automatically affect the quality improvement of school’s graduates. It indeed really depends on school management and teachers’ approaches. Therefore, some factors should be noticed seriously are students’ development, autonomy, democratic atmosphere, exploratory approach, freedom, students’ experiences, balance between social and individual quality of students, also emotional quotient as well as spiritual quotient.